Sprawl and Fragmentation. The case of Medellin Region in Colombia - Fabio Alberto Hernandez Palacio (TeMA: Journal of Land Use, Mobility and Environment, 2012)
Sprawl and fragmentation are phenomena common to many cities but they do have particularities depending on the geographic, economic and societal context.  This paper will examine the particularities of these two phenomena, intrinsically related, in the Aburra Valley (the metropolitan area of Medellin – Colombia).  The phenomena will be analyzed from their origins, their different manifestations and the possible solutions of control within this context. Low density and discontinuous urban growth is a matter of great interest to city governments, transport authorities, urban planners, economists, sociologists and environmentalists. From a technical view, sprawl is associated with negative effects such as larger commuting times and greater consumption of fuel, which also means increase of pollution; increase in capital investment to accommodate population growth in space; acceleration of inner-city urban decline due to the abandonment of former urban spaces, social segregation manifested in spatial mismatch of population (poor living in inner city, rich living in peripheral areas).  But from the citizen’s perspective, regardless of income, small low-density communities, which shape sprawl, are an ideal of living. This dichotomy with its implicit factors represents a big challenge to contemporary urban governance.